the role of posyandu cadres The Role of Posyandu Cadres in Toddler Health Services During the Covid-19 Pandemic, Jombor Village, Sukoharjo Regency: research on the role of posyandu cadres - Widati; Magdalena Asri Almuhasari (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
Health is a very important thing that can be used as one of the parameters that can determine the quality of human resources (HR) in a country, because through health services it can be seen from whether a country is progressing or not. Healthcare Center toddlers and Healthcare Center cadres during the pandemic play an important role in health services or health providers. There are 11 Healthcare Center in Jombor village with an average number of cadres in Healthcare Center as many as 5 people. The participation of cadres in Jombor Village in Healthcare Center activities during the pandemic in under-five health services can be addressed by moving back to the toddler Healthcare Center in Jombor Village after 6 months of not running as usual. The success of Healthcare Center Healthcare Center in Jombor Village can be seen from the performance or role of cadres in carrying out activities during the pandemic. The success that was carried out during this pandemic period was related to how the role and efforts of cadres in running Posyandu during the pandemic, namely cadres and village midwives carried out in different ways, namely Socialization, Mobilization, Coordination, Assistance and Cooperation in running Posyandu during the Covid-19 Pandemic.